2017
DOI: 10.11648/j.ajnna.20170304.11
|View full text |Cite
|
Sign up to set email alerts
|

Location Selection of Logistics Center in e-Commerce Network Environments

Abstract: Abstract:The site selection of logistics center is a very complicated and enormous system problem. Each site selection method and model is based on a certain premise and hypothesis. The site selection decision of distribution center has an important influence on the whole logistics system operation. A good location of urban logistics sites is important for optimizing the logistics network, and improving the urban traffic conditions, and level of logistics services. Motivated by this, in this paper, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Figure 1 is a scatter plot of dimensionless wave heights and periods ("wave height and period" in short). The maximum entropy probability density functions of wave height and period are respectively obtained by substituting the parameters of Table 1 into Equation (19)…”
Section: Double Entropy Joint Distribution Function and Engineering Amentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 is a scatter plot of dimensionless wave heights and periods ("wave height and period" in short). The maximum entropy probability density functions of wave height and period are respectively obtained by substituting the parameters of Table 1 into Equation (19)…”
Section: Double Entropy Joint Distribution Function and Engineering Amentioning
confidence: 99%
“…The corresponding parameters can be obtained through Equations (7) and (18), as shown in Table 1. The maximum entropy probability density functions of wave height and period are respectively obtained by substituting the parameters of Table 1 into Equation (19) and are as follows:…”
Section: Double Entropy Joint Distribution Function and Engineering Amentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the damage of coastal and ocean engineering are usually the result of their combined effect. Currently, the theory of multivariate distribution has been applied in many fields [10][11][12][13][14][15][16]. Many application examples have also shown that the design parameters derived from a joint probability distribution can better meet the design need of ocean engineering [17][18][19][20], reduce the building cost of ocean engineering more reasonably, explore return periods of multivariable waves, and calculate joint design level values more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Modern intellectual means of analysis and prediction allow, with sufficiently high accuracy, regardless of the subject area, to determine the development trend of the researched variables based on the processing of large arrays of source data and detecting implicit, hidden patterns [1,2]. There are works on neural network prediction of stock prices and currency rates [3,4], credit scoring tasks, business strategies and logistics of e-commerce centers [5,6,7], features of radio signal propagation [8], pattern, speech and emotion recognition [9,10,11,12], research in medicine [13,14]. Separate articles, describing the attempts to predict students' progress, were published [15].…”
Section: Introductionmentioning
confidence: 99%